Pericentral hepatocytes produce insulin‐like growth factor‐2 to promote liver regeneration during selected injuries in mice. Issue 6 (6th November 2017) - Liu, Junlai; Hu, Xiao; Chen, Jie; Li, Xinqi; Wang, Lu; Wang, Binbin; Peng, Wenbo; Yang, Cuiwei; Li, Zhijie; Chen, Yan; Wang, Yue J.; Li, Chuanjiang; et al.
Abstract : Liver regeneration (LR) happens after various types of injuries. Unlike the well‐studied LR caused by partial hepatectomy (PHx), there is accumulating evidence suggesting that LR during other injuries may result from unknown mechanisms. In this study, we found that insulin‐like growth factor 2 (IGF‐2) was drastically induced following the liver injuries caused by tyrosinemia or long‐term treatments of CCl4 . However, this was not observed during the early phase of acute liver injuries after PHx or single treatment of CCl4 . Remarkably, most IGF‐2‐expressing hepatocytes were located at the histological area around the central vein of the liver lobule after the liver injuries caused either in fumarylacetoacetate hydrolase–deficient mice or in CCl4 chronically treated mice. Hepatocyte proliferation in vivo was significantly promoted by induced IGF‐2 overexpression, which could be inhibited by adeno‐associated virus–delivered IGF‐2 short hairpin RNAs or linsitinib, an inhibitor of IGF‐2 signaling. Proliferating hepatocytes in vivo responded to IGF‐2 through both insulin receptor and IGF‐1 receptor. IGF‐2 also significantly promoted DNA synthesis of primary hepatocytes in vitro . More interestingly, the significantly induced IGF‐2 was also found to colocalize with glutamine synthetase in the region enriched with proliferating hepatocytes for the liver samples from patients with liver fibrosis. Conclusion: IGF‐2 is produced by pericentral hepatocytes to promote hepatocyte proliferation and repair tissue damage in the setting of chronic liver injury, which is distinct from the signaling that occurs post‐PHx. (Hepatology 2017;66:2002–2015)